2019
DOI: 10.1016/j.impact.2019.100151
|View full text |Cite
|
Sign up to set email alerts
|

Surface coating determines the response of soybean plants to cadmium sulfide quantum dots

Abstract: Quantum dots (QDs) are used in an array of applications from electronic devices to medicine, leading to environmental release and accumulation in landfills and agricultural soils. However, their effects on plants have been least studied among other engineered nanomaterials. In the current study, soybean seedlings were exposed to 50-200 mg/L cadmium sulfide quantum dots (CdS-QDs) to elucidate their bioaccumulation and biological response in comparison to Cd 2+ ions and bulk-CdS. To understand the role of surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 61 publications
2
32
0
Order By: Relevance
“…24 In a recent study, we exposed soybean plants to CdS-QDs without any coating or coated with different ligands including a water-soluble polymer (polyvinylpyrrolidone, PVP), a hydrophobic ligand (trioctylphosphine oxide, TOPO), a thiol compound (mercaptoacetic acid, MAA) and an amino acid (glycine, GLY) in vermiculite media. 12 Exposure to CdS-QDs coated with MAA or GLY resulted in Cd accumulation in soybean root cell walls, whereas CdS-QDs coated with TOPO were unstable due to the hydrophobicity of the ligand and released Cd 2+ ions that accumulated in cell membranes. In contrast, PVP coating on the CdS-QDs enabled efficient transport of the particles or Cd 2+ to root organelles and aerial tissues, leading to reduced leaf biomass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 In a recent study, we exposed soybean plants to CdS-QDs without any coating or coated with different ligands including a water-soluble polymer (polyvinylpyrrolidone, PVP), a hydrophobic ligand (trioctylphosphine oxide, TOPO), a thiol compound (mercaptoacetic acid, MAA) and an amino acid (glycine, GLY) in vermiculite media. 12 Exposure to CdS-QDs coated with MAA or GLY resulted in Cd accumulation in soybean root cell walls, whereas CdS-QDs coated with TOPO were unstable due to the hydrophobicity of the ligand and released Cd 2+ ions that accumulated in cell membranes. In contrast, PVP coating on the CdS-QDs enabled efficient transport of the particles or Cd 2+ to root organelles and aerial tissues, leading to reduced leaf biomass.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 However, only a small fraction of Cd 2+ from QDs is dissolved in contrast to soluble Cd-compounds at equimolar Cd concentrations. 12 Hence, the Cd availability from QDs is generally overestimated and the specific mechanism of toxicity of QDs remains unclear. In planktonic bacteria (Pseudomonas aeruginosa), CdSe QDs were found to be more toxic by generating more intracellular reactive oxygen species (ROS) than soluble Cd salts, at equivalent Cd concentrations of 20-125 mg L −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the influence of exposure duration on Cd-based QDs toxicity is insufficiently understood [ 19 , 20 ]. Only a limited number of studies have analyzed and compared the impacts of CdS QDs and Cd ions on whole organism development, as well as on organ, tissue or cellular structure [ 21 , 22 , 23 , 24 ]. Marmiroli et al [ 14 , 25 ] characterized the transcriptomic and changes associated with exposure to CdS QDs in A. thaliana ; two mutants ( atnp01 and atnp02 ) of Landsberg erecta , collection Soll-Jonson, with Ac/Ds maize transposon insertion, were identified as tolerant to CdS QDs but not to Cd 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…The proteins most affected by the CdS-QDs are components of mitochondrial respiration complexes III, IV and V. Mitochondria are a significant organelle in QD-induced toxicity [ 67 , 68 ]. It has been shown that CdS QDs damage mitochondrial functionality and reduce respiration activity in yeast [ 24 ], plants [ 22 ], and human cells [ 21 ]. Damage to mitochondrial functions and structure caused by several types of metal-ENMs has been reported in mollusc bivalve and mouse cells [ 69 , 70 ].…”
Section: Resultsmentioning
confidence: 99%